Sustainable agriculture : organic farming vs. chemical based farming practices in Serian, Sarawak - Dayang Filidia, Abang Ahmad Bolhassan. (Universiti Malaysia Sarawak (UNIMAS), 2006)
Agriculture has played a key role in the development of modern Malaysia, resulting in the country becoming the world's leading palm oil producer and the third largest producer of natural rubber. Agriculture continues to make a significant contribution to the national economy. In 2003, the agriculture sector registered a growth of 5.5 percent, following in importance after the manufacturing and the service sectors. In 2004, the government of Malaysia declared the agriculture sector to be the third engine of growth. Following this promising status of agriculture, many modern and large scale agricultural farming are encouraged to be applied by existing farmers and also to newly open farms. In this frenzied state to agriculture, many concerns on the wisdom of opening more lands for agriculture, especially on massive mono - crop plantation such as oil palm, or maintaining natural state of virgin lands. Appalling decisions may raise unseen problems such as depleting state of soil conditions. Thus, more sustainable agricultural practices likely to be applied in such huge farms will help in reducing problems with soil conditions and also pollution. At present, organic agricultural practices have increasingly becoming the new trend for attaining sustainable agriculture system in the country. Farms such as in Cameron Highlands are converting their practices from intensive chemical - based farming to more natural based organic farms. This scenario occurs thus relating to the increasing environmental problems of chemical - based practices due to pollution of chemical leaching to its surrounding natural resources and also the unsustainable state of its soil quality. In Sarawak, organic farming practices have been applied in many farms but many of these farms are not certified or have not applied to be certified as a fully organic farms, still these are in the minority compared to other non - organic practices such as intensive chemical - based farming and the traditional shifting agriculture that are also more known to the general public. This study tries to illustrate the existence of organic farms, particularly in the Serian area, and compare the general sustainability factors of these farms to the adjacent intensive chemical - based farming. Common soil parameters for assessing soil quality and fertility namely soil texture, soil reaction (pH) and soil organic matter content are used in the search for comparing the soil status in both fanning practices. As expected, the farms that employ organic practices are found to have better soil conditions than the chemical - based farms that seem to be ailing in their soil health status compared to the secondary forest soils in the area. The sustainability of both fanning practices are also discussed with particular reference to the impact of the practices to the environment. Overall, it was concluded that sustainable agriculture which includes organic farming practices is more considerate to the environment as a whole and it also implies far longer cultivation period in any fain land thus provides the choice of not having to worry about opening and destroying more precious virgin forests.